Pravastatin for Prevention of Preterm Birth in High-Risk Pregnancies: A Pilot Randomized Controlled Trial - Muhammad Ilham Aldika Akbar; Ayu Diah Primaningrum (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Objective: This research aims to evaluate the feasibility, safety, and preliminary efficacy of pravastatin for preventing preterm birth among high-risk pregnant women. Methods: This double-blind, randomized, placebo-controlled pilot trial was conducted at a tertiary referral center in Indonesia (August 2024–June 2025). Pregnant women at 14–28⁺⁶ weeks' gestation with ≥1 preterm birth risk factor were randomized 1:1 to oral pravastatin 20 mg twice daily or placebo until delivery. The primary outcome was preterm birth <37 weeks. All analyses were conducted on an intention-to-treat basis.Results: Thirty-five women were analyzed (pravastatin n=17; placebo n=18) with comparable baseline characteristics. Preterm birth <37 weeks was significantly lower in the pravastatin group (11.8% vs 72.2%; OR 0.051, 95% CI <0.01–0.31; p=0.001), with higher median gestational age at delivery (37 vs 34.5 weeks; p=0.005). Pravastatin was also associated with reduced preterm preeclampsia (11.8% vs 55.6%; p=0.006), higher neonatal birthweight (3227 ± 628 g vs 2446 ± 373 g; p<0.001), and lower rates of low birthweight (5.9% vs 77.8%; p<0.001). No significant differences in neonatal adverse outcomes were observed.Conclusion: In this small pilot trial (n=35), pravastatin was associated with a reduced incidence of preterm birth and improved gestational and neonatal outcomes among high-risk pregnancies. Given the small sample size, the very large observed effect sizes should be interpreted with caution and may reflect random variation. These preliminary findings support the feasibility and safety of pravastatin in this population and provide justification for larger, adequately powered randomized controlled trials.Pravastatin untuk Pencegahan Kelahiran Prematur pada Kehamilan Berisiko Tinggi: Uji Coba Terkontrol AcakAbstrakTujuan: Penelitian ini bertujuan mengevaluasi kelayakan, keamanan, dan efikasi awal pravastatin dalam mencegah persalinan prematur pada ibu hamil berisiko tinggi.Metode: Uji klinis pilot tersamar ganda, acak, terkontrol plasebo ini dilakukan di pusat rujukan tersier di Indonesia (Agustus 2024 – Juni 2025). Ibu hamil dengan usia kehamilan 14 – 28⁺⁶ minggu yang memiliki ≥1 faktor risiko persalinan prematur diacak 1:1 untuk menerima pravastatin oral 20 mg dua kali sehari atau plasebo hingga persalinan. Luaran utama adalah persalinan prematur <37 minggu. Seluruh analisis dilakukan berdasarkan prinsip intention-to-treat.Hasil: Sebanyak 35 ibu hamil dianalisis (pravastatin n=17; plasebo n=18) dengan karakteristik dasar yang sebanding. Persalinan prematur <37 minggu secara bermakna lebih rendah pada kelompok pravastatin (11,8% vs 72,2%; OR 0,051; IK 95% <0,01 – 0,31; p=0,001), disertai median usia kehamilan saat persalinan yang lebih tinggi (37 vs 34,5 minggu; p=0,005). Pravastatin juga berhubungan dengan penurunan preeklamsia prematur (11,8% vs 55,6%; p=0,006), berat lahir neonatus yang lebih tinggi (3227 ± 628 g vs 2446 ± 373 g; p<0,001), serta penurunan angka berat lahir rendah (5,9% vs 77,8%; p<0,001). Tidak terdapat perbedaan bermakna pada luaran neonatal yang merugikan.Kesimpulan: Pada uji klinis pilot berskala kecil ini (n=35), pravastatin berhubungan dengan penurunan insiden persalinan prematur serta perbaikan luaran gestasional dan neonatal pada kehamilan berisiko tinggi. Mengingat jumlah sampel yang kecil, effect size yang sangat besar harus diinterpretasikan dengan hati-hati karena dapat mencerminkan variasi acak. Temuan awal ini mendukung kelayakan dan keamanan penggunaan pravastatin pada populasi tersebut, serta memberikan justifikasi untuk pelaksanaan uji klinis acak terkontrol berskala lebih besar dengan kekuatan statistik yang memadai.